Water quality and neurodegenerative disease risk in the middle-aged and elderly population - Yujia Bao; Yongxuan Li; Yanqiu Zhou; Jingqi Zhou; Wei Mu; Xiaobei Deng; Chen Shen; Lefei Han; Jinjun Ran (Ecotoxicology and Environmental Safety)
Ensuring sustainable management of water is an indispensable part of sustainable development, however, the limelight on long-term health risk of water hardness is essential but remains inadequate. This study estimated effects of water hardness on the brain system to refine its systemic risk assessment. We assembled a cohort of 397,265 participants from the UK Biobank to investigate the associations of water hardness with neurodegenerative diseases and brain imaging phenotypes through modeling. We found water hardness in 0–120 mg/L elevated the incidence risks of Alzheimer’s disease and vascular dementia compared to that in 120–300 mg/L, with hazard ratios of 1.13 (1.01, 1.27) and 1.24 (1.05, 1.46), respectively. Furthermore, the associations with partial cerebral atrophy were also observed, including the caudate nucleus and inferior parietal lobule. Our study provides insights into the importance of enacting more precise guidelines about water hardness and contributes to the achievement of the Sustainable Development Goals.